STRUCTURAL AND PHOTOOXIDATION PROPERTIES OF SNO2/LAYER SILICATE NANOCOMPOSITES - Korösi L.; Németh J.; Dékány I. (My University, 2004)
SnO2 nanoparticles were prepared by hydrolysis in aqueous medium and stabilized by montmorillonite or hectorite. The tin content of SnO2/clay nanocomposites varied between 15 and 50 wt.%. Intercalation of tin dioxide nanoparticles between the lamellae of the minerals was verified by X-ray diffraction. Calcination temperature of the samples was changed in the range of 80–1000 °C. It was shown by N2 gas adsorption measurements that as temperature was increased, the specific surface area of the catalysts (80–210 m2/g) markedly decreased. The presence of SnO2 particles measuring 2–6 nm was verified by transmission electron microscopy, atomic force microscopy, X-ray diffraction, dynamic light scattering. The photooxidative efficiency of SnO2/clay photocatalysts was investigated by degradation of salicylic acid. It was established that the catalytic effect is mainly due to the presence of nanosized tin dioxide particles. By selecting the appropriate experimental conditions, we accomplished size-controlled synthesis of nanocrystalline tin dioxide surpassing microcrystalline SnO2 in catalytic activity.
Keywords: Tin dioxide; Layer silicates; Montmorillonite; Hectorite; Adsorption; Intercalation; Nanoparticles; Photocatalysis